1999
DOI: 10.1103/physrevlett.82.4988
|View full text |Cite
|
Sign up to set email alerts
|

Charge Form Factor of the Neutron from the Reaction2H(e

Abstract: We report on the first measurement of spin-correlation parameters in quasifree electron scattering from vector-polarized deuterium. Polarized electrons were injected into an electron storage ring at a beam energy of 720 MeV. A Siberian snake was employed to preserve longitudinal polarization at the interaction point. Vector-polarized deuterium was produced by an atomic beam source and injected into an open-ended cylindrical cell, internal to the electron storage ring. The spin correlation parameter A V ed was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
166
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(173 citation statements)
references
References 28 publications
6
166
1
Order By: Relevance
“…Passchier et al [Pas99] reported the first measurement of spin-correlation parameters A V ed at a Q 2 of 0.21 GeV 2 in 2 H( e, e ′ n)p reaction at NIKHEF; this experiment used a stored polarized electron beam and an internal vector polarized deuterium gas target; they extracted the value of G En from the measured sideways spin-correlation parameter in quasi-free scattering.…”
Section: Neutron Electric Form Factor Measurements With Polarization mentioning
confidence: 99%
“…Passchier et al [Pas99] reported the first measurement of spin-correlation parameters A V ed at a Q 2 of 0.21 GeV 2 in 2 H( e, e ′ n)p reaction at NIKHEF; this experiment used a stored polarized electron beam and an internal vector polarized deuterium gas target; they extracted the value of G En from the measured sideways spin-correlation parameter in quasi-free scattering.…”
Section: Neutron Electric Form Factor Measurements With Polarization mentioning
confidence: 99%
“…This shows that in this specific kinematic region the deuteron can be used as an effective neutron target. Thus, these data were normalized to the calculations and yielded an absolute accuracy of 3% in the determination of hP d 1 for our measurement of the charge form factor of the neutron [37]. For increasing missing momenta, both the data and predictions for the asymmetry reverse sign.…”
mentioning
confidence: 99%
“…The second wall was used only for neutron detection, as described in Ref. [37]. central angle of 58 ± and covered a solid angle of about 250 msr.…”
mentioning
confidence: 99%
“…A number of other cuts was applied to optimize the dilution factor and keep the nuclear corrections under control. [3], open diamonds [4], open cross [5], open circle [6], open triangle [7], open squares [8]). …”
Section: Analysis and Resultsmentioning
confidence: 99%